If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10x + -1(4 + 5x) = 0 10x + (4 * -1 + 5x * -1) = 0 10x + (-4 + -5x) = 0 Reorder the terms: -4 + 10x + -5x = 0 Combine like terms: 10x + -5x = 5x -4 + 5x = 0 Solving -4 + 5x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + 5x = 0 + 4 Combine like terms: -4 + 4 = 0 0 + 5x = 0 + 4 5x = 0 + 4 Combine like terms: 0 + 4 = 4 5x = 4 Divide each side by '5'. x = 0.8 Simplifying x = 0.8
| 19x=40-x | | y-x=54 | | 60+X=5X+6 | | 6x+6y+0z=2900 | | 3x-9-5-x=6 | | 7x+6=3b+29 | | (10x-5)+(2x+6)= | | 3(x-3)-(5-x)=6 | | 2y=6x+17 | | y=(3x^3+1)(-4x^2-3) | | 8uv+2+4vu+8= | | X^2+30x+90=0 | | y=-.375x^2+7.5x+0 | | 15m-5n+10= | | x+2a=12+ax-6a | | 25x-81y=0 | | q+32-7(80)=0 | | 8k-106=8k+10 | | Qo+32-7(80)=0 | | 5x-153=237+3x | | 4x=(-3x+1.5)-1 | | 7x^3-3x-4=0 | | 3(x-6)-21=x-4 | | 5B=c-ab | | B=c-ab | | 6+5(7-2)= | | (2b+7b-1)-(b-2b-4)=18 | | 7.5x-1.2=28.8 | | 21+2x=-13+3x | | 2b-5b+b= | | 4x+9x=130 | | 3(x-6)-21=3x-39 |